Techniques and methodologies for railway capacity analysis: comparative studies and integration perspectives - Kontaxi, Evangelia (Univerzita Pardubice, 2010)
The article provides an analysis of methods and techniques for the qualification of the railway capacity, classified by reference to factors having a direct relationship with the obtained results. Synthetic, analytical and analogical methods are compared and developed.
Keywords: capacity; methodologies; techniques